Українсько-турецькі торговельні зв’язки початку XVIII ст.: види та походження товарів - Станіславський, В. (Чорноморська минувшина, 2015)
У статті автор зосереджує свою увагу на аналізі інформації про види товарів у торговельних зв’язках України та Туреччини на початку XVIII ст. Також проаналізовано походження хутра, яке було одним із основних товарів, які продавали в Туреччину. Джерельною базою дослідження стали документи російського посольства в Османській імперії. Materials of the Russian Embassy in the Ottoman Empire have saved data on the most important and most expensive goods that brought merchants from Ukraine to Turkey. There are also facts about goods that were transported from Turkey to Ukraine and transported by transit to Russia. The highest demand in Turkey had fur products. The most expensive fur like sable was of Russian origin. Part of the less expensive fur was Ukrainian origin. Sometimes merchants brought so much fur that the market was oversaturated. From Turkey to Ukraine Greek merchants transported fabrics and some items of clothing, carpets, weapons and other luxury goods like gems. These goods came from Turkey and from outside the country. В статье автор сосредотачивает свое внимание на анализе информации о видах товаров в торголе между Украиной и Турцией в начале XVIII в. Также проанализированы происхождения меха, который был одним из основных товаров, продававшихся в Турцию. Ключевой базой исследования стали документы российского посольства в Османской империи.